Community Empowerment through LDPE Waste-Based Paving Block Technology, Financial Viability and SDGs Contribution in Kedaung, Bandar Lampung - Martinus Martinus; An-Nisa Magnolia; Eko Wahyu Saputa; Rizal Adi Saputra; Syaipudin Anwar; Sony Ferbangkara; Sabiqunassabiqun Sabiqunassabiqun; Agung Widi Utomo; Randa Admiral; Reihan Baskoro (Jurnal Masyarakat Madani Indonesia, 2026)
The growing accumulation of low-density polyethylene (LDPE) plastic waste and the limited competitiveness of the local paving block industry in Kedaung, Bandar Lampung, have created an urgent need for innovative and community-based solutions. This study aims to implement and evaluate a participatory technology transfer program for producing LDPE-reinforced paving blocks while ensuring optimal financial feasibility and environmental sustainability. The community service program was conducted on February 7, 2026, using a Participatory Action Research (PAR) approach that actively involved local residents throughout the planning, implementation, and evaluation processes. The program consisted of several integrated activities, including a technology demonstration, hands-on production training, a business feasibility workshop, and the initiation of a community-based production unit. The results indicated that the established community business group achieved a projected profit margin of 21.2%, with a break-even point of approximately 220 paving block units per month. In addition to enhancing local production capacity and entrepreneurial skills, the program contributed to the achievement of five Sustainable Development Goals. Overall, the integrated empowerment model demonstrated strong financial viability, environmental benefits, and potential applicability as a replicable circular economy initiative for other urban communities facing similar waste management and economic challenges